A NON-GOVERNMENTAL LANGUAGE IN THE BOOK PUBLISHING OF WESTERN AND SOVIET BELARUS (1921–1939): AN ATTEMPT OF COMPARATIVE ANALYSIS - Dovnar, Larisa (Knygotyra, 2016)
The article aims at providing an analysis of the peculiarities of book publishing in national languages in Western and Soviet Belarus within the context of political events during the period of 1921–1939. Statistical and source analysis methods have been used to analyse linguistic situation in the fields of education (schools) and publishing. Such analysis makes it possible to more comprehensively understand the situation in question, defining the need for books in various ethnic groups and describing the particularities of book publishing policy in Belarus SSR and West Belarus, which was part of the Polish state. According to statistical data, ethnic composition of the population both in Belarus SSR and Western Belarus, with the majority being Belarussians, Poles, Jews and Russians, was similar in 1920–1930. The article seeks to compare the policy of education in ethnic languages; qualitative data of national Belarus, Jewish, Ukrainian, Lithuanian and other ethnic schools in BSSR and Western Belarus as well as the changes in their development. A more comprehensive analysis is provided on the statistical data about Belarus schools and book publishing in Western Belarus. Starting with the 30-ties of the 20th century, the education policy with regard to ethnic groups in BSSR was becoming more restricted; schools gradually shifted to instruction in the Russian language. Russian gained dominance in book publishing as well. The period of 1921–1929 was the most favourable for satisfying the needs of ethnic minorities both in Belarus SSR and Western Belarus. During the above mentioned period, ethnically engaged literature, including the ethnic literature for schools, belles-letters and informational literature was prevailing in BSSR. Thus, in 1925–1926, publishing of literature in the Belarus language accounted for 68 percent, in Jewish – 15 percent, in Russian – 10 percent, in Polish – 5 percent, in Lithuanian – 2 percent, of all the volumes of publishing, in both parts of Belarus, respectively. However, at a later time, publishing in Russian started to grow increasingly. During the period of 1932–1939, publishing in the Russian language increased even by 27 times. Such changes were aimed at implementing the policy of sovietisation and denationalization. In Western Belarus, the main channel of spreading the Belarussian word was the periodical press. The development of the Belorussian book both in BSSR and Western Belarus was directly dependent on the political policy. Books in the ethnic languages can be defined as a tool of political propaganda. At the same time, publications in the native ethnic languages helped national minorities maintain their ethnic and cultural identity and resist assimilation attempts.